2022
DOI: 10.2337/db22-217-or
|View full text |Cite
|
Sign up to set email alerts
|

217-OR: A Randomized Controlled Trial Comparing the Safety and Efficacy of IDegLira vs. Basal Bolus in Patients with Poorly Controlled Type 2 Diabetes and Very High HbA1c (>9%–15%) : IDegLira HIGH Trial

Abstract: IDegLira-HIGH trial was a non-inferiority, prospective, randomized clinical trial, comparing the efficacy and safety of insulin degludec/liraglutide combination (IDegLira) and a regimen of multiple daily injections (MDI) with basal-bolus insulin (BB) in adults (>18-80 years of age) , with type 2 diabetes (T2D) , and very high HbA1c (>9%-15%) , previously treated with basal insulin or multiple oral agents. Primary endpoint was change in HbA1c from baseline to week 26. Secondary endpoints included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…30 Furthermore, IDegLira has recently emerged as a valid and simple alternative to a complex BB insulin regimen for patients with T2D and poorly controlled diabetes, as documented by very high HbA1c (9%-15%). 31 The extent of HbA1c reductions in both groups of patients was consistent with that obtained in other Italian observational studies 21,22 and similar to that reported in the European retrospective study, 25 but also with the results of the randomized controlled trials of the DUAL programme. [7][8][9][10][11][12] In DUAL-V, patients on basal-only insulin randomized to IDegLira had a greater HbA1c reduction of 0.6% than those randomized to continuing and uptitrating basal insulin.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…30 Furthermore, IDegLira has recently emerged as a valid and simple alternative to a complex BB insulin regimen for patients with T2D and poorly controlled diabetes, as documented by very high HbA1c (9%-15%). 31 The extent of HbA1c reductions in both groups of patients was consistent with that obtained in other Italian observational studies 21,22 and similar to that reported in the European retrospective study, 25 but also with the results of the randomized controlled trials of the DUAL programme. [7][8][9][10][11][12] In DUAL-V, patients on basal-only insulin randomized to IDegLira had a greater HbA1c reduction of 0.6% than those randomized to continuing and uptitrating basal insulin.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, IDegLira is also economically advantageous up to a dosage of 25 units compared with the BB combination 30 . Furthermore, IDegLira has recently emerged as a valid and simple alternative to a complex BB insulin regimen for patients with T2D and poorly controlled diabetes, as documented by very high HbA1c (9%‐15%) 31 …”
Section: Discussionmentioning
confidence: 99%
“…HbA1c decreased in both groups from 10.8% to 7.7%, but significantly fewer receiving degludec/liraglutide had an episode of glucose<70 mg/dl (22% vs. 36%) and the former had significant weight loss of 3.7 kg versus weight gain of 8.4 kg, albeit with significantly greater likelihood of nausea (12% vs. 1%). 28 McCrimmon et al 29 compared 814 T2D persons receiving insulin glargine/lixisenatide combination versus 814 propensity score matched T2D persons receiving basal‐bolus treatment, finding somewhat lesser HbA1c decrease from 9.2%, by 0.7% versus 0.8%, and significant weight difference at 0.1 kg weight loss versus 0.7 kg weight gain.…”
Section: Incretin‐based Therapiesmentioning
confidence: 99%